Comparison of flight behaviour and flight morphology between perching Lycaena phlaeas and patrolling Zizeeria maha (Lepidoptera: Lycaenidae) - Michio IMAFUKU (European Journal of Entomology, 2025)
Perching (territorial) and patrolling are recognised as mate-locating tactics adopted by male butterflies. It is said that males adopting the former fly fast with high acceleration, whereas those adopting the latter fly at continuous and lower speeds. However, no previous studies have demonstrated these flight properties using quantitative data. In the present study, the flight properties of two lycaenid species, the perching L. phlaeas and the patrolling Z. maha, were investigated based on three-dimensional analysis. Males of L. phlaeas had higher flight velocities and higher relative flight time than those of Z. maha. Furthermore, the flight morphology that supports flight properties was examined. The perching L. phlaeas exhibited higher thorax-to-body mass ratios and greater wing loadings than patrolling Z. maha.